Assessing the effect of crop residue removal on soil organic carbon storage and microbial activity in a no‐till cropping system. (18th September 2015) - Chowdhury, S.; Farrell, M.; Butler, G.; Bolan, N.
Abstract: Changes in agricultural management strategies have received much attention in recent years with a view to increasing or maintaining the amount of carbon (C) sequestered as soil organic C (SOC). In many parts of the world, minimum or no‐till management has been promoted as a means of improving soil quality, reducing losses of erosion and potentially increasing SOC stocks. However, no‐till systems can become problematic and potentially disease‐prone, especially due to high crop residue loadings. Consequently, residue removal either by harvesting or burning off may be employed to reduce these pressures. Here, we examined the effect of crop residue removal on C storage in soil that had been under no‐till management for 20 yr. We predicted improved physical properties (i.e. lower bulk density) and greater microbial activity under the residue retention soils due to greater readily available C and nutrients derived from crop residues. In contrast, we predicted relative reductions in SOC in the no residue soils due to a lack of available residue‐derived C for microbial use. Residue removal caused a relative C loss from the soil, which was related to C input, amount of nutrient availability and microbial activity. We demonstrate the importance of maintaining crop residue cover in no‐till cropping systems for soil function and highlight the potentially deleterious effects of changing management strategy to increased residue harvesting or removal by burning.